2018
DOI: 10.3390/ijms19092825
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Protective and Anti-Melanogenic Effects of Loliolide and Ethanol Extract from Fresh Water Green Algae, Prasiola japonica

Abstract: Loliolide is a monoterpenoid hydroxylactone found in many algae, including fresh water green algae, Prasiola japonica. To date, loliolide and compounds in P. japonica have not been studied systematically with respect to skin pharmacology. In this study, we investigated oxidative stress-protective and anti-melanogenic effects of loliolide and P. japonica ethanol extract (Pj-EE), known to contain loliolide, in human keratinocyte (HaCaT) cells and mouse melanoma (B16F10) cells. Loliolide suppressed the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…However, studies scrutinizing the antioxidant and anti-inflammatory activities of the isolated terpenes are scarce. For instance, loliolide has been recently reported to suppress oxidative stress and increase the expression of heme oxygenase-1 in H 2 O 2 -induced HaCaT cells [96].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies scrutinizing the antioxidant and anti-inflammatory activities of the isolated terpenes are scarce. For instance, loliolide has been recently reported to suppress oxidative stress and increase the expression of heme oxygenase-1 in H 2 O 2 -induced HaCaT cells [96].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, research with photoprotective compounds that can confer protection against ROS-induced cell death has become important today. As we showed in our previous study, loliolide exhibited a strong antioxidant activity [25]; since antioxidant compounds often exhibit photoprotective activity as well, in this research, we wanted to determine whether loliolide also had a photoprotective effect. Loliolide, apart from showing no cytotoxic effects in concentrations of up to 100 µg/mL (Figure 2a), showed promising photoprotective activity, since it increased cell survival when subjected to UVB radiation (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Loliolide (Figure 1) is an active ingredient in green algae that has been shown to have antioxidant, cellular protection [22,23] anticancer [24], and cell senescence inhibition [24] activities. In our previous study, we also showed that loliolide demonstrates important antioxidant and antimelanogenic activity, suggesting its potential as a treatment for skin diseases [25]; however, research related to its effects on UV-damaged skin is still lacking [26]. Prasiola japonica ethanol extract (Pj–EE) is a loliolide-rich source that has also been shown to possess antioxidant activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Loliolide, a monoterpenoid hydroxylactone contained in Prasiola japonica , suppressed gene expression of matrix metalloproteinases ( MMP s), Nrf2 , and HO-1 in HaCaT Keratinocytes stimulated by H 2 O 2 [ 88 ].…”
Section: Plant-derived Natural Nrf2 Modulators For Skin Protectionmentioning
confidence: 99%
“… Terpenoid compounds activating the Nrf2-mediated pathway [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. …”
Section: Figurementioning
confidence: 99%